Analisis Faktor-Faktor Pertumbuhan Keuangan Hotel Menggunakan Metode Analisis Keuangan Statis Dan Dinamis (Studi Kasus: PT Hotel Mandarine Regency Tbk) - Atun Yulianto - AKPAR BSI Yogyakarta (Khasanah Ilmu - Jurnal Pariwisata Dan Budaya, 2012)
Planning is one of the functions of management, planning, hotel operations in the future it would be best if supported by relevant financial information. The quality of economic decisions in the planning will be increased if supported by the analysis of financial statements better. With the method of analysis of financial statements, both static and dynamic reading will assist management in the company's financial growth trends. Good results of the analysis can be used as a basis for planning and predictions about what will happen in the future. PT Hotel Mandarine Regency Tbk is one business that is engaged in providing hospitality services in Indonesia. From the results of analysis of its financial statements indicate a trend decline in financial performance of the hotel, to the hotel management need to improve the quality of planning the future activities to be more effective and efficient. Improved financial performance is necessary to provide assurance of liquidity, solvency, and profitability is good to investors who have invested their funds in the company. Keyswords : Financial Statement, liquidity, solvency, profitability